The Florida times-union (Florida Pub. Co., 1903)
The Jacksonville (FL) Florida Times-Union [LCCN sn83045831] enjoys the reputation of being the oldest continuously published newspaper in Florida; this fact's even been solicited for inclusion in contest questions for the television game show, Jeopardy. It has had, however, multiple changes of title during this time. It began publication as the Florida Union [LCCN sn83016252] in 1864. The newspaper went several iterations of this title as it went through changes between variant titles. In 1883, the two existing Jacksonville (FL) newspapers, the Florida Daily Times [LCCN sn83016248] and the Daily Florida Union [LCCN sn83016241], combined. The combined title, too, published under several variant titles, some in several iterations as well. A detailed listing of the mergers and acquisitions and assorted editors during the 19th and early 20th centuries may be found among the Elmer J. Emig Papers in the Special and Area Studies Collections at the George A. Smathers Libraries on the campus of the University of Florida in Gainesville (FL). At any rate, in 1903, the Florida Times-Union and Citizen [LCCN sn87062267] became the Florida Times-Union, again and has continued under the same title through current day (ca. 2008). In post-Civil War Florida, when most papers were avowedly Democratic, the Florida Times Union maintained a Republican editorial stance. Until 1983, when Morris Communications purchased Florida Publishing Company, the newspaper had been one of Florida's largest and most widely circulated independent newspapers. The Florida Times-Union became the largest newspaper of this chain, which (ca. 2008) owns a number of newspapers around the country. For a considerable period the Florida Times-Union was owned by the Florida East Coast Railroad. Displaying an unrelenting partisanship, the paper was well known for back page coverage of rail accidents and invariably giving the front page to trucking accidents. An oft repeated joke around Jacksonville was that "In North Florida, trains don't hit cars. Cars hit trains." In 1959, Florida Publishing Company, then its parent company, purchased Jacksonville's evening newspaper the Jacksonville (FL) Journal [LCCN sn84009348]. The Jacksonville Journal, itself, was heir to another of Florida revered ancient titles, the Metropolis (Jacksonville, FL) [LCCN sn82014370], later the Florida Metropolis [LCCN sn95026764], which published independently in Miami (FL) as well under the same titles. The Florida Times-Union and the Jacksonville Journal remained sister publications until 1988, when the Jacksonville Journal ceased publication. Jacksonville is the seat of county government for Duval County (FL). By 1903, the city was dusting itself off and rebuilding following the Great Fire of Jacksonville in 1901. Frank Lloyd Wright was one of the new city's architects. Rebuilding and the advent of tourism as an American vacation past-time strengthened Jacksonville's railroad connections both north-south and east-west. In 1906, with the opening of the Port of Jacksonville in the deep waters and wide mouth of the St. Johns River, Jacksonville's place as a major Florida city had become inevitable. Jacksonville's heritage as a military garrison traces back to the first French settlement, ill-fated though it was, at Fort Caroline. It's military importance heightened during the Civil War when it repeatedly changed hands between Confederate and Union forces. And again, in 1908, Jacksonville together with its northerly neighbor Fernandina (FL) (the present day, Fernandina Beach), anchored traffic to Cuba during both the Spanish American War and the (first) Cuban Revolution. Today (ca. 2008), Jacksonville continues to host several military bases.-- E. Kesse, University of Florida Digital Library Center.